Securitization performance model in Malaysia - Dabas, Nurayati; Bakri, Mohammed Hariri (International Organization of Scientific Research (IOSR), 2018)
In 1986,the Malaysian Securities Commission established Cagamas Berhad as the National Mortgage Corporation of Malaysia,based on the Fannie Mae and Freddie Mac guidelines or models in the United Stated.The objective of Cagamas Berhad is to develop the secondary mortgage market and to encourage home ownership in Malaysia. However,the growth of asset securitization in Malaysia is relatively slow because of originator hesitation,investor reluctance and the unclear position of the regulators. Thus,this study intends to fill the study gap that pertains to the performance of asset-backed securities firms in Malaysia.Most studies on the performance of securitization were done in other countries and they only focused on banks.However,no studies have been carried out on the performance of the firms,especially in Malaysia. Malaysia is currently suffering from the financial crisis and with the currency declining,not only is the performance of the securitized firms affected,the Malaysian economy is also adversely impacted.Several studies reported that banks have high performances because of Asset-backed Securitization and the commonly used method for financial analysis is the use of profitability ratios such as net profit,Return on Asset (ROA) and Return of Equity (ROE).